Managing strategic changes in personnel resistance to open innovation in companies - Oleksandr Bilichenko; Mikhail Tolmachev; Tetiana Polozova; Dmytro Aniskevych; Alzoubi Laith Abdel Karim Mohammad (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The aim of the work is to develop theoretical, methodological, and applied foundations and practical recommendations for managing strategic changes in personnel resistance to open innovations in companies. The following special methods were used in the research process: Comparative and economic-statistical analysis-to assess the level of unique, threshold, and average opportunities for resistance to changes in open innovation; ranking-to assess the development of corporate culture. The main method of study was expert evaluation through questionnaires. The experts were middle managers of five branches of international car companies in Poland: Fiat, Opel, Toyota, Volkswagen, and Volvo. The reason for choosing these companies is that they collectively occupy 85% of the Polish automotive market. Resistance to open innovations usually arises at the individual level of personnel and is addressed through informational and motivational measures. According to the study, the threat to strategic change management in companies is system resistance for Opel and Toyota. This allowed us to draw a conclusion on the development of a predominantly fiduciary corporate culture, which minimizes the resistance to open innovation in companies. Approbation of the approaches of the companies under study proved that in the current conditions, there is a combination of different types of strategies. Recommendations regarding the choice of change strategies are substantiated for all the companies under study.
Keywords: 650; corporate culture; intellectual capital; international company; model; personnel; resistance to open innovations